Las controversias sobre las competencias de la jurisdicción eclesiástica ante las órdenes militares en la Monarquía de España: algunas “allegationes” - Rodríguez Arrocha, Belinda (Jahrbuch für Geschichte Lateinamerikas, 2018)
The characteristics of Spanish military orders were debate topics for the jurists and theologians in the early Modern Age. The most important issue was the consideration of knights as ecclesiastical or lay individuals. The main purpose of this paper is the analysis of the "allegationes" belonging to the Palafoxiana library (Puebla), in regard to the judicial competences over the members of military orders. In this sense, two important examples are the "allegationes" prepared by Ambrosio Machín in Sardinia and by Juan de Morales Barnuevo in Castile in the first half of seventeenth century. These printed texts are interesting sources for the study of the circulation of the juridical debates between the Catholic Europe and New Spain. Its contents concerned the competences of ecclesiastical and secular jurisdictions and the conflicts between courts or authorities because of crimes perpetrated by military knights and novices. The doctrinal discussions about the juridical “status” of those individuals were transcendental during the Old Regime, due to the social projection of the taking of military vows in the territories subjected to the Spanish Crown. Furthermore, the mentioned texts spread in New Spain the canon and royal rules about the judicial competences in civil and criminal trials, also as the opinions of famous authors, such as Castillo de Bobadilla, García Mastrillo, and Farinacci.
Keywords: Sardinia; Legal History; Mexico; XVIIth Century